Reference values and biological determinants for cardiac myosin-binding protein C (cMyC) concentrations: Reference values and biological determinants - Krintus, Magdalena; Kozinski, Marek; Kloska, Sylwester M.; Bergmann, Katarzyna; Mankowska-Cyl, Aneta; Siodmiak, Joanna; Sypniewska, Grazyna (Journal of Medical Biochemistry, 2023)
Background: Cardiac myosin-binding protein C (cMyC) is a novel cardio-specific biomarker of potential diagnostic and prognostic value for cardiovascular events. The aim of this study is to determine reference values for cMyC and to identify biological determinants of its concentration. Methods: A population of 488 presumably healthy adults was enrolled to define biological determinants which affect cMyC concentrations in serum. Concentrations of cMyC were assessed using enzyme-linked immunosorbent assays from commercially available kits. Eligibility for inclusion in this study evaluated anthropometric, demographic and laboratory measurements in all subjects. After applying strict inclusion criteria, a reference population (n=150) was defined and used for the determination of reference values. Reference values were derived using a robust method. Results: The distribution of cMyC concentrations in the reference population was non-parametric, right-skewed, with only 2 subjects having concentrations lower than the limit of detection. Female gender was the only independent determinant of higher cMyC concentrations in the presumably healthy population. There were no significant relationships between cMyC and other investigated parameters in the reference population. The overall upper reference limit (URL) set at 99th percentile for cMyC concentration was 42.29 ng/mL and did not differ between women and men (42.52 vs. 42.35 ng/mL). Conclusions: This study successfully established reference values for the assessed cMyC assay and investigated its biological determinants. Despite the impact of female gender on cMyC concentrations in the presumably healthy population, we did not detect sex-dependent differences in the cMyC 99th URL and we therefore recommend the use of a single 99th URL for adults.